2020
DOI: 10.3390/ijerph17062122
|View full text |Cite
|
Sign up to set email alerts
|

Less Favorable Lipid Profile and Higher Prevalence of Thyroid Antibodies in Women of Reproductive Age with High-Normal TSH—Retrospective Study

Abstract: High-normal TSH can be associated with metabolic abnormalities and infertility. Aims of this study are to analyze retrospectively if routinely measured blood laboratory and anthropometric parameters differ between women of reproductive age with TSH < 2.5 mIU/L and with TSH ≥ 2.5 mIU/L. Retrospective analysis was performed in 466 female inpatients, aged 13–51, hospitalized in an endocrine department. The group of 280 patients with normal thyroid tests (TSH 0.27-4.2 mIU/L; normal FT3 and FT4) was selected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
3
7
0
4
Order By: Relevance
“…Such associations are expected concerning the mechanism of thyroid hormones action on lipid profile, and similar results were found by Knight and coworkers in a pregnant population [3]. It is worth mentioning that similarly to the association between IH and abnormal lipid profile, observed in the present analysis, we found the association between high normal TSH and abnormal lipid profile in the same population sample [25], and also in our earlier prospective studies performed in non-pregnant women of reproductive age [44,45]. Therefore, it can be concluded that both IH and high normal TSH (which is associated with only a relative decrease of thyroxine concentration) contribute to the abnormal lipid profile in women of childbearing age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such associations are expected concerning the mechanism of thyroid hormones action on lipid profile, and similar results were found by Knight and coworkers in a pregnant population [3]. It is worth mentioning that similarly to the association between IH and abnormal lipid profile, observed in the present analysis, we found the association between high normal TSH and abnormal lipid profile in the same population sample [25], and also in our earlier prospective studies performed in non-pregnant women of reproductive age [44,45]. Therefore, it can be concluded that both IH and high normal TSH (which is associated with only a relative decrease of thyroxine concentration) contribute to the abnormal lipid profile in women of childbearing age.…”
Section: Discussionsupporting
confidence: 92%
“…The steps of this retrospective study, including the patient characteristics, were described in detail elsewhere [25].…”
Section: Methodsmentioning
confidence: 99%
“…In some recent studies, researchers found that participants with high-normal TSH levels were associated with less favorable lipid profiles. 22 , 23 Li revealed that TSH within the reference range is positively associated with the risk of CAD; individuals with 2.5–5.5 mIU/L of TSH had a 4-fold risk of CAD compared with those with 0.3–0.9 mIU/L. 24 In our study, it was firstly concluded that TSH elevation within the normal range did not portend prognosis in STEMI.…”
Section: Discussionmentioning
confidence: 52%
“…Although still not recommended, a few studies have proposed lowering the threshold of TSH for diagnosing subclinical hypothyroidism from the conventional 4-5 mIU/L to 2-2.5 mIU/L [30][31][32][33][34] . Recently, women with high normal TSH levels (> 2.5 mIU/L) were found to have unfavorable lipid profile, oxidative damage of membrane lipids and low levels of mannanbinding lectin, all of which are associated to infertility and adverse pregnancy outcomes [32][33][34] . When using the lower threshold of 2.5 mIU/L, 70 (27.5 %) patients in this study could be considered hypothyroid.…”
Section: Discussionmentioning
confidence: 99%